INTEGRASI CERITA RAKYAT DALAM PEMBELAJARAN BAHASA DAN SASTRA: TINJAUAN SISTEMATIS LITERATUR TERHADAP PENINGKATAN NILAI BUDAYA DAN IDENTITAS LOKAL - Simanungkalit, Kaleb E.; Simanjuntak, Berliana; Sinaga, Sannur Hayati; Panggabean, Leben (Universitas Hamzanwadi, 2025)
This study examines the integration of folklore into Indonesian language and literature learning to enhance students' understanding of cultural values and local identity. In the era of globalization, folklore is often neglected despite its significant cultural value. This study aims to explore how the use of folklore can increase students' cultural awareness and enrich language and literature learning. A Systematic Literature Review (SLR) approach was employed, using the PICO-S framework (Population, Intervention, Comparison, Outcome, and Study Design). The findings indicate that integrating folklore enhances students' understanding of local culture and fosters their engagement in learning. The use of technology, such as Mixed Reality and web-based learning materials, strengthens learning effectiveness, although the cultural values acquired through traditional methods remain significant. In conclusion, folklore is an effective educational tool for reinforcing cultural identity and student literacy in Indonesian language and literature learning, particularly amid the challenges of globalization and technological advancements.